A Biomimetic Hybrid Hydrogel Based on the Interactions between Amino Hydroxyapatite and Gelatin/Gellan Gum. Issue 9 (6th August 2020) - Wang, Lvyang; Li, Mengya; Li, Xiumin; Liu, Jie; Mao, Yajie; Tang, Keyong
Abstract: In this work, a gelatin (Gel)‐oxidized gellan gum (OG)/amino hydroxyapatite (mHap) hybrid hydrogel with Schiff base linkages is reported. The mHap is obtained by modifying hydroxyapatite with tetraethyl orthosilicate and 3‐aminopropyl‐triethoxysilane. The effects of different mHap contents on the structure, morphology, and properties of hydrogels are particularly investigated. Scanning electron microscopy coupled with energy dispersion spectroscopy reveals that mHap of around 100 nm is uniformly distributed inside the hydrogel with interconnected porous structures. Notably, the hydrogel with 1 wt% mHap possesses the highest compressive stress (2.01 ± 0.10 MPa) at 90% strain, as well as the lowest equilibrium swelling ratio (97% ± 5%) and degradation rate than other hydrogels. Besides, an ultra‐high compressive stress equivalent to 91% of the initial stress can be obtained by this hydrogel after 50 loading‐unloading cycles (85% strain). Meanwhile, after being swollen, this improved hydrogel also exhibits better structural stability than Gel‐OG hydrogel. The in vitro 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay further shows that all hydrogels are nontoxic against mouse fibroblasts. This work provides a biomimetic strategy to construct the organic/inorganic hydrogels with excellent interactions, elasticity, reversibility, and biocompatibility, which is of great importance for the practical applications in cartilage tissue engineering. Abstract : A gelatin‐oxidized gellan gum/amino hydroxyapatite (mHap) hybrid hydrogel with excellent interactions, elasticity, and reversibility is prepared based on Schiff base linkages. The mHap is obtained by modifying hydroxyapatite with tetraethyl orthosilicate and 3‐aminopropyl‐triethoxysilane. This hybrid hydrogel has great biocompatibility as well, which is proposed to have potential applications in cartilage tissue engineering.